2016
DOI: 10.1177/1365480216631080
|View full text |Cite
|
Sign up to set email alerts
|

Towards a democratic school: The experience of secondary school pupils

Abstract: This article sets out to explore how young people understand and experience the notions of democracy and participation in their secondary schools. We draw on their own words to examine their perspective on participation in everyday life at school to understand what kind of democratic education they are participating in. The article forms part of the Demoskole 1 project, which studies democracy and the participation of school community members in secondary schools in Catalunya (Spain). To date, our fieldwork su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
9
0
8
Order By: Relevance
“…As we have argued elsewhere (Simo´, Parareda & Domingo, 2016), in the current social and political context, the definition of democracy in schools is both ambiguous and problematic.…”
Section: Democracy and Educationmentioning
confidence: 99%
“…As we have argued elsewhere (Simo´, Parareda & Domingo, 2016), in the current social and political context, the definition of democracy in schools is both ambiguous and problematic.…”
Section: Democracy and Educationmentioning
confidence: 99%
“…Demokratik bir eğitim ortamı oluşturabilmek için öğrenme sürecinde öğrenciyi merkeze alan, onların derse aktif katılımlarını destekleyen, öğrenmenin nasıl gerçekleşeceği konusunda onlara seçme şansı veren yaklaşımların kullanılması gereklidir. Öğrencileri araştırmaya teşvik etmek, çeşitli bakış açılarını fark ederek karşılaştırmalarını sağlamak, eleştirel düşünmeye ve ulaştıkları bilgileri sorgulama yönlendirmek, kendi söylemlerini oluşturmalarını sağlamak ve daha sonrasında bunları ifade edebilecekleri ortamlar oluşturmak öğrenci merkezli yaklaşımların ortak özelliklerindendir (Gallop, Krapf & Weidinger, 2010;Jacobs ve Power, 2016;Kovacs, 2009;Simó, Parareda & Domingo, 2016). Öğrencilerin demokrasi kültürünü kazanmaları için okullar demokrasinin ilke ve kurallarının somutlaştırıldığı ortamlar olarak düzenlenmeli, öğrencilere düşünce ve ifade özgürlüklerini kullanma, yönetme ve karar alma mekanizmalarına katılma, yani demokrasiyi yaşama ortamları sağlanmalıdır (Gallop vd., 2010;Lind, 2019;Varnham, Evers, Booth & Avgoustinos, 2014).…”
Section: Introductionunclassified
“…Teachers believed that adopting democratic practices could positively impact their teaching efficiency (Schweisfurth, 2002), generate feelings of trust, empathy, and reflectiveness (Catalano & Leonard, 2016), and aid in the development of student agency and independence (McNamara, 2019). Findings from investigations involving the large-scale implementation of democratic processes indicated that students' positive attitudes toward school increased (Cleaver & Riddle, 2014), student well-being improved through collaborative studentteacher relationships (Simó et al, 2016), and future participation in traditional higher education environments was not affected negatively (Gray & Chanoff, 1986). At the classroom level, democratic educational practices have increased students' feelings of openness (McAvoy & Hess, 2013;Pennisi, 2013), empowerment and achievement (Simovska, 2011), problem solving and critical thinking skills (Brown, 2012), and agency, empathy, and reflection (Boatright & Allman, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers suggested that students' positive response to the school environment was likely based on a climate that encouraged student autonomy and personal responsibility. Even minimal implementation of democratic practices, such as a collaborative student-teacher relationship, has been found to positively affect school atmosphere and student well-being (Simó et al, 2016). Although large-scale implementation may be beneficial, the resources required can be a potential limiting factor for underfunded or understaffed schools such as those found in rural areas (Schmuck & Schmuck, 1990).…”
Section: School or Program-wide Implementationmentioning
confidence: 99%
See 1 more Smart Citation